Pengembangan Pusat Kuliner Nusantara Kota Bandung Sebagai Tujuan Wisata - Oda - STP BSI Bandung (Universitas Bina Sarana Informatika, 2012)
Bandung City as a students and industrial city has become attraction for people from other regions in Nusantara to visit it to study and look for a job. Heterogeneity of Bandung population, also as a constrainnt to manage, is a potential to develop as a the centre of Nusantara food that can support economic growth of Bandung City. The innitiative of nusantara food centre derives from some businesmen, not the government of Bandung City. Bandung city does not have Nusantara food centre map, either its origin or the kinds, because the exist of Nusantara food centre has not been identified. Nusantara food map availability is very important, it can make tourist easy to find the centre of Nusantara food and the government can carry out the retribution easily. Key Word: Nusantara Culanary, Touristsm Destination